Despite high‐risk exposures, no evidence of zoonotic transmission during a canine outbreak of leptospirosis. (7th January 2019) - Guagliardo, Sarah Anne J.; Iverson, Sally Ann; Reynolds, Laura; Yaglom, Hayley; Venkat, Heather; Galloway, Renee; Levy, Craig; Reindel, Alison; Sylvester, Tammy; Kretschmer, Melissa; LaFerla Jenni, Margaret; Woodward, Peter; et al.
Abstract: Leptospirosis is a bacterial zoonosis that affects many mammals, including humans and dogs; dogs can transmit the bacteria to humans, but the frequency of transmission and highest risk exposures are poorly understood. During 2016–2017, the Maricopa County Department of Public Health, Arizona Department of Health Services and Centers for Disease Control and Prevention investigated the zoonotic potential of a canine leptospirosis outbreak in the Phoenix metro area. We identified symptomatic persons exposed to canine leptospirosis cases by conducting active and passive surveillance. We tested dog owners ( n = 9) and animal care providers ( n = 109) for serological evidence of Leptospira spp. infection (via the microscopic agglutination test [MAT]) and interviewed these persons about their specific exposures to canine cases and general exposures to canine blood and urine. Through surveillance, seven symptomatic persons were identified; six were tested and all were negative by MAT, and of these six, four persons were negative by PCR (two did not have PCR testing). All serosurvey participants ( n = 118) were also seronegative. Among animal care providers, bare skin contact with urine/blood from a canine case was reported by 23.2%; two persons reported dog urine splashing in their face. Veterinary technicians were more likely to have bare skin contact with blood from a canine case compared to veterinarians and boarding facility staff ( p < 0.001). Infection control practices were inconsistent; when working with specimens from a canine leptospirosis case, 44.6% of participants reported always wearing gloves when working with urine (i.e., collecting specimens), and 54.5% always wore gloves when working with blood. Veterinary technicians were also most likely to engage in all activities involving potential urine/blood contact, such as conducting laboratory tests ( p < 0.01). We therefore recommend that veterinary technicians specifically receive targeted education about infection control practices. Our results suggest that dog‐to‐human transmission of leptospirosis is uncommon.